ENGKANA MASUK PADI DAN IDENTITAS MASYARAKAT DAYAK KUBITN DI KABUPATEN MELAWI PROVINSI KALIMANTAN BARAT - Karlina, Fransiska; Effendy, Chairil; Martono, Martono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research presents a study that focuses on the study of oral literature, namely engkana masuk padi. The rapid development of Science and Technology has led to a reduction in engkana speakers, so that it is possible for the next few years this tradition will disappear. A study of oral literary texts engkana masuk padi is needed so that it can be preserved. The focus of the problem in this study is the cultural values, functions, and engkana masuk padi identity. The method used in this study is descriptive analysis. The steps of data collection are done by recording, transcribing, editing, translating, identifying, classifying, interpreting, and concluding. The results of the analysis of cultural values that describe the relationship between humans and God are the existence of offerings. Human relations with oneself, namely hard work, developing work ethics and learning, never give up, patience, honesty and wisdom. Human relations with the surrounding nature, namely the use of natural resources. Human relations with each other, namely mutual cooperation, caring, willing to sacrifice, be helpful, forgive, love, and devote to parents. The results of function analysis, namely: as a way to convey the origin of events; as a means to inherit trust; as a projection system; as a means to inherit traditional living procedures, customs and habits; as a means of forcing and supervisors so that the norms of society will always be obeyed by their collective members; and as a means of releasing social pressures. The results of identification identity of the Kubitn Dayak community are: The Kubitn Dayak community as an agrarian community; The Kubitn Dayak community as an religion community; The Kubitn Dayak community as a solider community; and The Kubitn Dayak community as an ecological community.Â Keywords: Engkana, masuk padi, identity, Dayak Kubitn.